"Don't Believe the Hype": Complicating the Thriving Quotient for Latino Undergraduate Men at Selective Institutions. Issue 6 (16th February 2018) - Okello, Wilson Kwamogi; Pérez, David
Abstract : Wilson Kwamogi Okello and David Pérez II apply the concept of public and hidden transcripts to challenge the apparent success of Latino male undergraduates.